2021
DOI: 10.1111/1742-6723.13863
|View full text |Cite
|
Sign up to set email alerts
|

Vascular injury is an infrequent finding following non‐fatal strangulation in two Australian trauma centres

Abstract: Objective: Non-fatal strangulation assessment is challenging for clinicians as clear guidelines for evaluation are limited. The prevalence of non-fatal strangulation events, clinical findings, frequency of injury on computed tomography angiogram (CTA) and outcomes across two trauma centres will be used to improve this assessment process. Methods: This is a retrospective observational study of adult presentations during 2-year period to two major-trauma referral hospitals and subsequent 12 months to identify de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Although Buitendag et al [6] reported that 59% of their cohort had abrasions on the neck, our findings indicate higher numbers (n=28, 82.4%). However, in another study, LMs were found in 163 cases (38.4%) [11].…”
Section: Discussionmentioning
confidence: 85%
“…Although Buitendag et al [6] reported that 59% of their cohort had abrasions on the neck, our findings indicate higher numbers (n=28, 82.4%). However, in another study, LMs were found in 163 cases (38.4%) [11].…”
Section: Discussionmentioning
confidence: 85%
“…The predominant injury mechanism was manual strangulation (97%) [ 1 3 , 5 , 10 ]. The predominant context of strangulation was intimate partner violence for women (75%) and assault for men (88%) [ 4 ], and most strangulation survivors had no (71%) or only minor injuries (21%) [ 1 3 , 5 , 10 ].…”
Section: Discussionmentioning
confidence: 99%